2018
DOI: 10.5897/ajar2017.12227
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of soil characteristics under four cropping and land management systems in south west Nigeria

Abstract: Soil degradation and desertification pose a major threat to agricultural production in sub-Saharan Africa. The influence of cropping systems which had been established on selected physical and chemical properties of soil were investigated in Akinyode-Okinni community in Egbedore Local Government Area (LGA) of Osun State, Nigeria. The cropping systems included agri-silviculture (SCM), silvi-pasture (SPC), agri-horti-silviculture (PAH) and agroforestry (AFT) selected from existing farms in the community. The sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…At the polyculture site, restoration with SI improved the soil biophysiochemical properties, as demonstrated by significantly increased (Kruskal-Wallis and Generalized Linear Model [GLM]; p.adj < 0.05) soil DNA abundances, fractional vegetation cover (FVC), hydraulic properties (1/Ks), electrical conductivity (EC), macronutrients (C, N, P, Mg, and Ca), micronutrients (Fe, Zn, and Co), and other helpful elements (Ti and Al; Figures 1C, 1D, S1F, and S2A) 26,27 . Still, a significant gap exists between the recovered nutrient level and the arable topsoil (Figure S2A) 28,29 . The DI method was not as effective but showed significantly increased ( p.adj < 0.05) DNA abundance, FVC, and hydraulic properties over time (Figures 1C and S2B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the polyculture site, restoration with SI improved the soil biophysiochemical properties, as demonstrated by significantly increased (Kruskal-Wallis and Generalized Linear Model [GLM]; p.adj < 0.05) soil DNA abundances, fractional vegetation cover (FVC), hydraulic properties (1/Ks), electrical conductivity (EC), macronutrients (C, N, P, Mg, and Ca), micronutrients (Fe, Zn, and Co), and other helpful elements (Ti and Al; Figures 1C, 1D, S1F, and S2A) 26,27 . Still, a significant gap exists between the recovered nutrient level and the arable topsoil (Figure S2A) 28,29 . The DI method was not as effective but showed significantly increased ( p.adj < 0.05) DNA abundance, FVC, and hydraulic properties over time (Figures 1C and S2B).…”
Section: Resultsmentioning
confidence: 99%
“…The SD region showed drastically different network characteristics in almost every category (Figure S4C). Keystone taxa, playing crucial roles in a community (Methods), were identified from the SD (3) and SI (28) regions, which belonged to Proteobacteria, Euryarchaeota, and Thaumarchaeota (Figure S4D). These results demonstrated that archaea are critical in community structure besides bacteria.…”
Section: Si Enhances the Microbial Community Stability At The Polycul...mentioning
confidence: 99%
“…The study of the potential for soil carbon in this land use can be used as an effort to create and monitor in the future for revegetation and soil protection in order to raise soil carbon stocks. Previous research from Lamidi et al (2018) divided soil depth on a scale: 0-15, 15-30, 30-45, and 45-60 cm for SOC sequestration studies. Research by Susanti et al (2021) also conducted a study of SOC in the Blang Bintang sub-district in Aceh Besar district.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most of these studies are conducted early in spring and autumn, less often in summer, as due to intense mineralisation of plant residues and organic matter in the soil, the content of N min significantly increases (Aurangojeb et al, 2017;Friesen, Cattani, 2017;Tripolskaja et al, 2017). This increase mainly occurs in the upper 0-30 cm soil layer (Deng et al, 2016;Wasiu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%